Label-Free Comparative Proteomics Analysis Revealed Heat Stress Responsive Mechanism in Hypsizygus marmoreus - Xu, Lili; Guo, Lizhong; Yu, Hao (Frontiers in Microbiology, 2021)
Heat stress is an important adverse environmental stress that influences the growth and development of Hypsizygus marmoreus (white var.). However, the molecular basis of heat stress response in H. marmoreus remains poorly understood. In this study, a label-free comparative proteomic technique was applied to investigate the global protein expression profile of H. marmoreus mycelia under heat stress. Confocal laser scanning microscope observation revealed that mycelia underwent autolysis and apoptosis under heat stress. Autolysis was mediated by upregulating the expression of cell wall degradation enzymes and inhibiting cell wall synthesis enzymes, and apoptosis might be induced by ROS and activation of caspases. TBARS analysis indicated that ROS was accumulated in H. marmoreus mycelia under heat stress. H. marmoreus induced the antioxidant defense system by upregulating the expression of catalases, superoxide dismutases, and peroxidases to prevent oxidative damage. MAPK cascade was found to be involved in heat stress signal transduction. The stress signal induced a ubiquitous defense response: inducible expression of different kinds of heat shock proteins. Trehalose synthesis enzymes were also upregulated, suggesting the accumulation of stress protector trehalose under heat stress. Besides, upregulated proteasome was identified, which could prevent the accumulation of non-functional misfolding proteins. To satisfy ATP depletion in heat response cellular processes, such as ROS scavenging, and protein folding and synthesis, enzymes involved in energy production (carbon metabolism and ATP synthesis) system were upregulated under heat stress. Taken together, these findings improve our understanding of the molecular mechanisms underlying the response of heat stress in H. marmoreus.